Fire Control Application for Technical Control of Artillery Fire – Data Binding - Martin Blaha (Journal of Systemics, Cybernetics and Informatics, 2017)

(untitled)
The Czech Republic, as a member of international organizations (NATO, EU, UNO), with respect to current global security neighborhood, employs the units of the army both at its own state territory and outside the Czech Republic, in multinational forces operations. The article focuses on Data Binding Issue of future Automated Command, Control, and Information system (C2I) in conditions of the Army of the Czech Republic. The issue of automated command, control, and information systems is of high importance in the solving of asymmetrical operations tasks today and in the upcoming future. The authors define ground for designing a new and by the Army of the Czech Republic required, sophisticated Automated Fire Support Control System of Artillery meeting NATO standards in Network Enabled Capabilities (NEC) conditions. Final assessment of the particular issues is determined by analysis. The software model contains derivation, definition and reasoning of data which are essential for the effective artillery fire in condition of modern software tool - Data Binding. The Czech Artillery units need to have intuitive system for mathematical computations which assures prediction capabilities for adequate fire support provision - PVNPG-14M. This software should be the best choice in current conditions. The article represents section of a huge defensive research project of Ministry of Defence of the Czech Republic and the Army of the Czech Republic solved by leading scientists of the University of Defence in Brno.